Self-identification of culture in the national education system ( in the context of the relationship of globalization and mass culture - Kotsuibanska, Olga (My University, 2012)
Тези присвячені проблемам національної ідентифікації в контексті глобалізованого світу та масової культури.Abstracts are devoted to the problems of national identity in the context of a globalized world and popular culture.
Keywords: глобалізація; самоідентифікація; освіта; масова культура; глобализация; самоидентификация; образование; массовая культура; globalization; identity; education; popular culture; кафедра гуманітарних дисциплін